1590. A Hybrid CMV Prevention Strategy Is Effective in Preventing CMV Disease Outcomes in Pediatric Solid Organ Transplant Patients. (26th November 2018) - Ore, Lucia Dalle; Boothroyd, Derek; Gans, Hayley; Chen, Sharon F
Abstract: Background: Optimal CMV prevention strategies for pediatric solid-organ transplant (SOT) patients have not been clearly defined for early and late post-transplant periods. Methods: We analyzed CMV prevention strategies in liver, kidney, heart, lung and intestinal SOT patients from 2005 to 2015 in our institution. A hybrid strategy was defined as prophylaxis for ≤6 months post-transplant and then transition to a pre-emptive strategy. Results: Of 833 patients, 769 were prophylaxis and 62 were hybrid strategies. Compared with prophylaxis, hybrid patients were more likely to have a D−/R− CMV serology status, be ≤1 year old and have a heart transplant ( P < 0.001). We found no significant differences in CMV disease frequency, rejection or mortality between hybrid and prophylaxis groups. In total, we found 13 cases of CMV disease, of which 1 was a hybrid and the rest a prophylaxis strategy. The median time to CMV disease was 1.5 years from transplant. We found more allograft rejection ( n = 9) in patients with CMV disease compared with patients with CMV infection or no Infection. For the same comparisons, no significant difference was found for age or type of organ transplant. Late rejection was frequent ( n = 6/13, 67%) in patients with CMV disease, and the majority were not started on empiric anti-virals with the rejection episode. In contrast, no CMV disease was found in patients who had late rejection and received empiric anti-viral with the rejection episode, even though these patients had increasing CMV DNAemia ( P = 0.04). Conclusion: In the early post-transplant period, a hybrid CMV prevention strategy is effective with similar clinical outcomes compared with a prophylaxis strategy, even in younger CMV naïve patients and relatively more immune suppressed heart transplant patients. A hybrid strategy may provide effective long-term control of intermittent CMV replication as suggested by the low frequency of CMV disease in this group compared with prophylaxis. In the late post-transplant period, administering episodic empiric anti-virals with a rejection diagnosis may be necessary to prevent CMV disease associated with late rejection episodes. Disclosures: All authors: No reported disclosures.